Abu Yusuf's Thoughts on Monetary Policy: a Critical Analysis of Inflation, Interest Rates, and Indonesia's Fiscal-Monetary Coherence in 2025 - Ainul Mardhiah (Modern Islamic Studies and Sharia Research, 2025)
The phenomenon of global monetary instability in the aftermath of the COVID-19 pandemic, compounded by the energy and food crises, has driven countries to strengthen the credibility of their monetary policies. Indonesia is no exception, facing inflationary dynamics, exchange rate fluctuations, and the urgent need for fiscal-monetary coordination to sustain economic growth. In this context, the thought of Abu Yusuf, the foremost disciple of Abu Hanifah and the author of Kitab al-Kharj, becomes increasingly relevant. Abu Yusuf emphasized three fundamental pillars underpinning monetary stability: the integrity of the standard of value, market supervision, and fiscal justice aligned with monetary objectives. The purpose of this study is to describe the intellectual profile of Abu Yusuf, examine monetary policies during his era, and explore their relevance to contemporary monetary policy, particularly in Indonesia. This research employs a qualitative approach with a descriptive-exploratory design, grounded in library research of classical texts and modern literature, complemented by an analysis of the latest empirical data from Statistics Indonesia (BPS), Bank Indonesia, and international institutions. The findings demonstrate that Abu Yusuf’s principles remain embedded in Indonesia’s current monetary practice. Price stability within the target range, cautious interest rate easing, and coherent fiscal-monetary coordination in the 2025 state budget (APBN) represent the actualization of his classical message regarding honesty in value, market oversight, and fairness in economic burdens. Thus, Abu Yusuf’s thought carries not only historical significance but also provides a normative and ethical framework for future monetary policy strategies. Fenomena ketidakstabilan moneter global pasca pandemi COVID-19, ditambah krisis energi dan pangan, mendorong negara-negara untuk memperkuat kredibilitas kebijakan moneter mereka. Indonesia tidak terkecuali, menghadapi dinamika inflasi, fluktuasi nilai tukar, serta kebutuhan koordinasi fiskal-moneter agar pertumbuhan ekonomi tetap berlanjut. Dalam konteks ini, pemikiran Abu Yusuf, murid utama Abu Hanifah dan penulis Kitāb al-Kharāj, menjadi relevan untuk dibaca kembali. Abu Yusuf menekankan tiga pilar utama yang menopang moneter: integritas standar nilai, pengawasan pasar, serta keadilan fiskal yang selaras dengan moneter. Tujuan penelitian ini adalah mendeskripsikan profil pemikiran Abu Yusuf, menelaah kebijakan moneter pada zamannya, serta mengeksplorasi relevansinya dengan kebijakan moneter kontemporer, khususnya di Indonesia. Penelitian menggunakan pendekatan kualitatif dengan desain deskriptif-eksploratif, berbasis studi pustaka terhadap teks klasik dan literatur modern, serta analisis data empiris terbaru dari BPS, Bank Indonesia, dan lembaga internasional. Hasil penelitian menunjukkan bahwa prinsip Abu Yusuf tetap hidup dalam praktik moneter Indonesia saat ini. Stabilitas inflasi di kisaran sasaran, pelonggaran suku bunga yang hati-hati, serta koordinasi fiskal-moneter dalam APBN 2025 merupakan bentuk aktualisasi dari pesan klasik tentang kejujuran nilai, pengawasan pasar, dan keadilan beban ekonomi. Dengan demikian, pemikiran Abu Yusuf bukan hanya memiliki nilai historis, tetapi juga memberi kerangka normatif dan etis bagi strategi kebijakan moneter ke depan.